Biochemical, quantitative and qualitative phenolic compounds, anti-free radical's activities of Calligonum comosum collected from different sites in the Algerian Desert - KHELEF, Y; CHOUIKH, A; REBIAI, A; NEFFAR,S; CHEFROUR, A; ADJAL, E.H; ALIA,F. (My University, 2019)
he aim of this study is to understand the effect on biochemical, quantitative and qualitative phenolic content and to estimate the anti-free radical's activities of the Calligonum comosum collected from various locations in Oued Souf region (Southeastern Algeria). Concerning the biochemical parameters, we registered pH values ranged between 4.8 and 4.2 and we observed oscillate in the amounts of proteins and the values of Catalase activity. The analysis of extracts by HPLC identified 43 compounds were counted as the maximum number of compounds, also we recorded the appearance of some phenolic compounds: Gallic acid, Chlorogenic acid, Vanillic acid, p-Comaric acid, Vanillin and Rutin in some extracts. Anti-free radical's activities which worked in two tests: DPPH● and TAC the results indicated that all extracts were highly anti-free radicals. Our results showed that there is a significant difference between the samples of Calligonum comosum collected in different sites